ORAL HEALTH EDUCATION IN THE CLASSROOM AND IT’S INFLUENCE ON COMPETENCIES AND HEALTH HABITS OF YOUNG ADULTS IN SRI LANKA (Isagoge - Journal of Humanities and Social Sciences, 2021)
The prevalence of Oral Health (OH) problems among the young adults in Sri Lanka is at a high level (Institute of Oral Health, 2018). The competencies on oral health obtain at the school may have a significant impact on the oral health habits of the new generations. The aim of this study is to investigate influence of science and health education in the school environment on the level of competencies and health habits towards OH among young adults in Sri Lanka. Survey design was followed to undertake the study. Both qualitative and quantitative (mixed) approaches used to conduct this study. Seven Dental Clinics were conveniently selected and from those seven clusters of dental clinics 107 young adults (15 years to 25 years) were selected randomly. Seven dentists and five science and health subject teachers were selected purposively. Questionnaire was used to collect data from young adults. Further on, in depth interviews with dental practitioners as well as science and health subject teachers were conducted to review both the vulnerability of the issue and how far the classroom education could influence the OH of students when they grow up as young adults. Statistical analysis method for quantitative data and thematic analysis method for qualitative data were used to identify the results. These results show that OH competencies are lower in young adults of Sri Lanka and school education on OH can significantly effect on improving the OH of individuals. OH education given to the students at the classroom is very important, because this awareness would help them lifelong to improve their quality of life free of many common oral heath burdens.
Keywords: Oral health education; School education; Health habits; Young adults